Apache II Score as a Predictor of Mortality and Length of Treatment for Generalized Peritonitis Patients at Dr. Kariadi General Hospital Semarang Indonesia - Ginting, Boni Aditia; Bernardus Parish Budiono (Open Access Indonesian Journal of Medical Reviews, 2022)
Peritonitis can cause sepsis and septic shock, which can lead to death. The existence of a prognostic assessment to assess the progression of cases of peritonitis becomes urgent. This is due to the fact that peritonitis progresses very quickly, and delays in treatment and action will cause the patient's death. This study is a preliminary study with the aim of assessing the potential for developing the APACHE II score as a predictor of mortality in generalized peritonitis patients at Dr. Kariadi General Hospital Semarang Indonesia. This study is an observational study with as many as 22 research subjects, peritonitis patients at Dr. Kariadi General Hospital Semarang Indonesia. Univariate and bivariate analysis was conducted to determine the relationship between APACHE II score with mortality and length of treatment. The results of the study showed that the APACHE II score was positively correlated with moderate strength and statistically significant to the mortality of generalized peritonitis patients. APACHE II score is able to predict mortality but is not able to predict the length of treatment for generalized peritonitis patients at Dr. Kariadi General Hospital Semarang Indonesia.